2023
DOI: 10.1038/s41398-023-02419-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma DYRK1A with aging may protect against neurodegenerative diseases

Abstract: Early markers are needed for more effective prevention of Alzheimer’s disease. We previously showed that individuals with Alzheimer’s disease have decreased plasma DYRK1A levels compared to controls. We assessed DYRK1A in the plasma of cognitively healthy elderly volunteers, individuals with either Alzheimer’s disease (AD), tauopathies or Down syndrome (DS), and in lymphoblastoids from individuals with DS. DYRK1A levels were inversely correlated with brain amyloid β burden in asymptomatic elderly individuals a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that it is involved in the development of many diseases, and both low and high expression levels of the DYRK1A protein contribute significantly to disease pathology [ 61 ]. A recent study suggests that elevated plasma levels of DYRK1A might help prevent neurodegenerative diseases [ 62 ], highlighting the potential value of this target in detecting, monitoring, and managing neurodegenerative disorders. As PTSD is a chronic mental disorder, there is a theoretical basis to further explore the role of DYRK1A in neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that it is involved in the development of many diseases, and both low and high expression levels of the DYRK1A protein contribute significantly to disease pathology [ 61 ]. A recent study suggests that elevated plasma levels of DYRK1A might help prevent neurodegenerative diseases [ 62 ], highlighting the potential value of this target in detecting, monitoring, and managing neurodegenerative disorders. As PTSD is a chronic mental disorder, there is a theoretical basis to further explore the role of DYRK1A in neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%